2019
DOI: 10.1186/s12885-019-5916-6
|View full text |Cite
|
Sign up to set email alerts
|

HBV-related hepatocarcinogenesis: the role of signalling pathways and innovative ex vivo research models

Abstract: Background Hepatitis B virus (HBV) is the leading cause of liver cancer, but the mechanisms by which HBV causes liver cancer are poorly understood and chemotherapeutic strategies to cure liver cancer are not available. A better understanding of how HBV requisitions cellular components in the liver will identify novel therapeutic targets for HBV associated hepatocellular carcinoma (HCC). Main body The development of HCC involves deregulation in several cellular signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 141 publications
0
63
0
Order By: Relevance
“…It remains to be determined if this localized hyperactive Wnt signaling is due to loss of transcriptional repression or activation of transcription. Further investigation of the p22 mechanism of action in ex vivo models systems for example that do not have the limitations of continuous, transformed cell lines and mouse models with respect to human disease [27], might reveal novel avenues of research to help identify new components to selectively harness different aspects of Wnt signaling; for example, blocking oncogenic Wnt signaling while preserving the critical role Wnt signaling provides to ensure the correct regulation of stem cells and homeostasis of many epithelial tissues. Selective regulation of Wnt signaling is at the core of identifying druggable Wnt pathway targets, as the desired outcome for a cancer specific drug that inhibits Wnt is for the drug to allow normal physiological processes to proceed thus reducing the toxicity of a blanket approach of inhibiting Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined if this localized hyperactive Wnt signaling is due to loss of transcriptional repression or activation of transcription. Further investigation of the p22 mechanism of action in ex vivo models systems for example that do not have the limitations of continuous, transformed cell lines and mouse models with respect to human disease [27], might reveal novel avenues of research to help identify new components to selectively harness different aspects of Wnt signaling; for example, blocking oncogenic Wnt signaling while preserving the critical role Wnt signaling provides to ensure the correct regulation of stem cells and homeostasis of many epithelial tissues. Selective regulation of Wnt signaling is at the core of identifying druggable Wnt pathway targets, as the desired outcome for a cancer specific drug that inhibits Wnt is for the drug to allow normal physiological processes to proceed thus reducing the toxicity of a blanket approach of inhibiting Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…HBV has been suggested to signi cantly induce liver cancer [16]. However, the underlying regulatory mechanism of HBV-infected liver cancer has not been fully elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…All the above results show that the progression in cell cycle has a close relationship with HBV-HCC. These gene functions and the signaling pathways might interact with HBV and corporately affect the development of HCC, especially by regulating the cell cycles and proliferation [15]. Xia et al found that HBV parvoviral host factors (such as PPARA, CEBPB and RXRA) were upregulated upon infection and enriched in primary human hepatocytes in the G2/M phase, which supports that HBV may promote viral replication and a premalignant phenotype that predisposes infected hepatocytes to subsequent malignant transformation by deregulating the cell cycle [16].…”
Section: Discussionmentioning
confidence: 99%